Subsea processing as a tool for cost reduction of deepwater projects (Research, Society and Development, 2020)
In order that the production and profits of petroleum companies do not decline, new oil field need to be discovered and exploited. Many of these new discoveries are offshore deepwater fields. However, the drop in oil prices in the last few years has made this type of exploration, which is already challenging in itself, even more difficult, so that companies are postponing or even canceling several deepwater projects. Innovation, new technologies and new concepts of oil and gas production and processing are necessary to make deepwater projects feasible and increase their competitiveness. The aim of this paper was to analyze the subsea processing of oil production as a strategy to reduce both capital and operating costs to enable remote offshore exploration. In addition, a discussion of the benefits and challenges of this strategy was also presented. It also includes a case study at the Lula field, in Brazilian pre-salt. Results demonstrate that the use of subsea separation has great potential to reduce OPEX and CAPEX on offshore projects. The current case study demonstrates a cost reduction due to the investment in the separators of around US$ 6.1 billion, a reduction about 6 to 12 times in the power needed to lift the production and a reduction of about 5 to 7 times in the expenditures with natural gas as fuel for the evaluated scenarios.